Phase 1 Clinical Trial of a Conditionally Replication-Defective Human Cytomegalovirus (CMV) Vaccine in CMV-Seronegative Subjects. (2nd July 2019) - Adler, Stuart P; Lewis, Nicole; Conlon, Anthony; Christiansen, Mark P; Al-Ibrahim, Mohamed; Rupp, Richard; Fu, Tong-Ming; Bautista, Oliver; Tang, Huaping; Wang, Dai; Fisher, Alison; Culp, Timothy; et al.
Abstract: Background: A conditionally replication-defective human cytomegalovirus (CMV) vaccine (V160) derived from AD169 and genetically engineered to express CMV pentameric complex (gH/gL/pUL128/pUL130/pUL131) was developed and evaluated for phase 1 vaccine safety and immunogenicity in CMV-seronegative and CMV-seropositive adults. Methods: Subjects received 3 doses of V160 or placebo on day 1, month 1, and month 6. Four vaccine dose levels, formulated with or without aluminum phosphate adjuvant, were evaluated. Injection-site and systemic adverse events (AEs) and vaccine viral shedding were monitored. CMV-specific cellular and humoral responses were measured by interferon-gamma ELISPOT and virus neutralization assay up to 12 months after last dose. Results: V160 was generally well-tolerated, with no serious AEs observed. Transient, mild-to-moderate injection-site and systemic AEs were reported more frequently in vaccinated subjects than placebo. Vaccine viral shedding was not detected in any subject, confirming the nonreplicating feature of V160. Robust neutralizing antibody titers were elicited and maintained through 12 months postvaccination. Cellular responses to structural and nonstructural viral proteins were observed, indicating de novo expression of viral genes postvaccination. Conclusions: V160 displayed an acceptable safety profile. Levels of neutralizing antibodies and T-cell responses in CMV-seronegative subjects were within ranges observed following natural CMV infection. Clinical Trial Registration: . NCT01986010. Abstract : Conditionally replication-deficient hCMV vaccine (V160) derived from AD169 and genetically engineered to express CMV pentameric complex (gH/gL/pUL128-131) displayed an acceptable safety profile. Levels of neutralizing antibodies and T-cell responses in CMV-seronegative subjects were within ranges observed following natural CMV infection.